Sociology of da'wah in the era of Industry 4.0 and Society 5.0: Implications for contemporary da'wah in Indonesia - Rahmat, Efendi; Abidin, Yusuf Zainal; Mukarom, Zaenal; Setiawan, Asep Iwan (FISIP UIN SGD Bandung, 2025)
The development of information technology in the era of the Industrial Revolution 4.0 and Society 5.0 has transformed the landscape of Islamic da'wah in Indonesia. Da'wah is no longer confined to physical spaces such as mosques and religious study groups but has expanded into digital platforms through social media, podcasts, and other online channels. This article aims to analyze the transformation of da'wah in the context of social change due to digitalization and its implications for contemporary da'wah strategies in Indonesia. The study adopts a qualitative approach using literature review and descriptive-critical analysis of da'wah sociology theories such as Symbolic Interactionism, Diffusion of Innovations, Social Mediation, and Bourdieu's theory of Habitus and Social Capital. The findings show that digital da'wah in Indonesia faces challenges such as the spread of religious misinformation, digital extremism, and low levels of digital literacy among the public. On the other hand, technological advancements offer wider, more inclusive, and data-driven opportunities for da'wah. Within the framework of Society 5.0, da'wah must be oriented toward humanistic and contextual social solutions. Therefore, a sociological approach to da'wah is crucial to ensure that Islamic messages remain relevant and capable of addressing the challenges of the times. In conclusion, da'wah in the digital era must strategically and adaptively integrate technology, culture, and social understanding. Contribution: This article advances academic and practical understanding of how digital technologies are reshaping religious communication, positioning sociological analysis as crucial to developing effective and future-ready da'wah strategies in Indonesia.